Acrylic adhesives, films and flexible devices with good recovery properties

By developing an acrylic adhesive with good creep recovery performance at both normal and high temperatures, the problem of difficult recovery of existing adhesive films under high temperature conditions is solved, and the excellent bending and recovery performance of flexible devices in high temperature environments is achieved.

CN119775906APending Publication Date: 2025-04-08GUANGDONG CROWN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411953844.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing adhesive film has too large deformation under high temperature conditions, making it difficult to restore its original appearance after removing stress, affecting the service life of foldable equipment.

Method used

An acrylic adhesive with good recovery performance was developed. The adhesive has good creep recovery at both normal temperature and high temperature, including a creep value of more than 90% at 25°C, a recovery value of more than 85%, a creep value and recovery value of more than 80% at 65°C, and a loss tangent value of less than 65°C, and a loss tangent value of less than 25°C.

Benefits of technology

The adhesive exhibits excellent bending performance and creep recovery performance at both room temperature and high temperature, extending the service life of the flexible device, and under high temperature conditions, the deformation is lower than room temperature, and the loss tangent value is correspondingly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215439530000031
    Figure BDA0005215439530000031
  • Figure BDA0005215439530000051
    Figure BDA0005215439530000051
  • Figure BDA0005215439530000061
    Figure BDA0005215439530000061
Patent Text Reader

Abstract

The present invention relates to an acrylic adhesive, a film and a flexible device with good recovery performance. The acrylic adhesive has a creep value of more than 90% at 25°C and a recovery value of more than 85% at 25°C; a creep value of more than 80% at 65°C and a recovery value of more than 85% at 65°C; and a ratio of a loss tangent value tanδ(65°C) of the acrylic adhesive at 65°C to a loss tangent value tanδ(25°C) at 25°C, tanδ(65°C) / tanδ(25°C)<1. The acrylic adhesive has good creep recovery at room temperature and high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to an acrylic adhesive, a film and a flexible device with good recovery performance. Background Art

[0002] In recent years, with the popularity of foldable devices, adhesives suitable for the use characteristics of foldable devices are also in demand in the market. Generally speaking, the adhesive film with optical properties used in foldable devices needs to have durability against environmental changes and good creep recovery, especially to maintain good creep recovery under normal and high temperature conditions during the normal use of foldable devices, so as to extend the service life of foldable devices.

[0003] Currently, most adhesive films on the market will increase their deformation under the same stress conditions as the temperature rises. When the deformation is too large, it is difficult to restore the original appearance even after the stress is removed, which is not conducive to the use of folding equipment under high temperature conditions. Summary of the invention

[0004] In view of the shortcomings of the prior art, the first object of the present invention is to provide an acrylic adhesive with good recovery performance, wherein the acrylic adhesive has good creep recovery at room temperature and high temperature.

[0005] A second object of the present invention is to provide an adhesive film which has sufficient deformation at room temperature and high temperature and can restore its original appearance after the stress is removed.

[0006] A third object of the present invention is to provide a flexible device having the adhesive film, wherein the flexible device has a longer service life.

[0007] To achieve the first purpose of the present invention, the present invention provides an acrylic adhesive with good recovery performance, wherein the creep value of the acrylic adhesive at 25°C is more than 90%, and the recovery value at 25°C is more than 85%; the creep value at 65°C is more than 80%, and the recovery value at 65°C is more than 85%; the ratio of the loss tangent value tanδ(65°C) of the acrylic adhesive at 65°C to the loss tangent value tanδ(25°C) at 25°C is tanδ(65°C) / tanδ(25°C)<1.

[0008] It can be seen that the acrylic adhesive provided by the present invention has good bending performance and creep recovery performance under the conditions of 25°C and 65°C. The acrylic adhesive provided by the present invention is an acrylic adhesive that can take into account the excellent bending performance and excellent recovery performance of bending action under normal high temperature environment. The deformation amount of the acrylic adhesive of the present invention at a high temperature of 65°C is lower than the deformation amount at room temperature of 25°C, that is, the high temperature deformation amount under the same stress is lower than the room temperature deformation amount, and the loss tangent value at a high temperature of 65°C is lower than the loss tangent value at room temperature of 25°C. The present invention has good recovery performance at normal temperature and high temperature, overcoming the shortcomings of the prior art.

[0009] In some embodiments of the present invention, the storage modulus of the acrylic adhesive at -20° C. is less than 100 kPa, and the storage modulus at 65° C. is greater than 15 kPa. The acrylic adhesive has a low modulus at high temperatures and also has good recovery properties.

[0010] In some embodiments of the present invention, the acrylic adhesive has a creep value of more than 100% at 25°C, a recovery value of more than 95% at 25°C, a creep value of more than 85% at 65°C, and a recovery value of more than 90% at 65°C. The acrylic adhesive has better bending performance and creep recovery performance at room temperature and high temperature.

[0011] In some embodiments of the present invention, the ratio of the loss tangent value tanδ(65℃) of the acrylic adhesive at 65℃ to the loss tangent value tanδ(25℃) at 25℃ is less than 0.9. The acrylic adhesive has low energy loss when deformed at high temperature.

[0012] In some embodiments of the present invention, the storage modulus of the acrylic adhesive at -20° C. is less than 80 kPa, and the storage modulus at 65° C. is greater than 18 kPa. The acrylic adhesive has a low modulus at high temperatures and also has good recovery properties.

[0013] In some embodiments of the present invention, the acrylic adhesive comprises a (meth)acrylic acid copolymer having structural units derived from the following cyclopolymerizable monomers:

[0014]

[0015] Wherein R is a hydrocarbon group or a substituted hydrocarbon group.

[0016] By using a (meth)acrylic acid copolymer having the structural unit of the cyclopolymerizable monomer as the main adhesive, an adhesive having good bending performance and creep recovery performance at normal high temperature can be obtained. R in the structural formula of the cyclopolymerizable monomer can be, for example, an alkyl group or a cyclohexyl group.

[0017] In some embodiments of the present invention, the mass proportion of the structural unit of the cyclopolymerizable monomer in the (meth)acrylic acid copolymer is 0.5-10%. The use of the cyclopolymerizable monomer in a small amount can greatly improve the bending performance and creep recovery performance of the adhesive. The mass proportion of the structural unit of the cyclopolymerizable monomer in the (meth)acrylic acid copolymer can be, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0018] In some embodiments of the present invention, the (meth)acrylic acid copolymer further comprises structural units derived from alkyl acrylate and hydroxyalkyl acrylate. Alkyl acrylate and hydroxyalkyl acrylate can further adjust the flexibility and adhesion of the adhesive. The (meth)acrylic acid copolymer can be formed by photoinitiated copolymerization of multiple monomers including cyclopolymerizable monomers, alkyl acrylate and hydroxyalkyl acrylate under the action of a photoinitiator. The amount of the photoinitiator can be 0.05 to 0.5% of the total mass of the monomers.

[0019] In some embodiments of the present invention, the alkyl acrylate is selected from at least one of 2-ethylhexyl acrylate, n-butyl acrylate, lauryl (meth) acrylate, isooctyl acrylate, and isostearyl acrylate. The alkyl acrylate has a long-chain alkyl group and is a flexible monomer. In some examples, the alkyl acrylate is a mixture of 2-ethylhexyl acrylate and isostearyl acrylate, and the mass ratio of 2-ethylhexyl acrylate to isostearyl acrylate is (81-85):13. The hydroxyalkyl acrylate is selected from at least one of hydroxyethyl acrylate, hydroxybutyl acrylate, and hydroxypropyl acrylate. The hydroxyalkyl acrylate is a functional monomer with a hydroxyl group.

[0020] In some embodiments of the present invention, the mass proportion of the structural unit of alkyl acrylate in the (meth)acrylic acid copolymer is 80-98%. As the main comonomer in the (meth)acrylic acid copolymer, the mass proportion of the structural unit of alkyl acrylate in the (meth)acrylic acid copolymer can be, for example, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, etc. The mass proportion of the structural unit of hydroxypropyl acrylate in the (meth)acrylic acid copolymer is 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0021] In some embodiments of the present invention, the acrylic adhesive further comprises an acrylate oligomer, a crosslinking agent and a silane coupling agent. Additives such as acrylate oligomers, crosslinking agents and silane coupling agents are added to the (meth)acrylic copolymer to further improve the performance of the adhesive.

[0022] In some embodiments of the present invention, the mass of the acrylate oligomer is 2-5% of the mass of the (meth)acrylic acid copolymer, for example, 2%, 3%, 4%, 5%, etc. The weight average molecular weight of the acrylate oligomer is 2000-9000 g / mol, preferably 3000-8000 g / mol; the molecular weight distribution of the acrylate oligomer is below 2.7. The above-mentioned acrylate oligomer can improve the adhesion of the adhesive while also giving it good optical properties.

[0023] In some embodiments of the present invention, the mass of the crosslinking agent is 0.1-0.5% of the mass of the (meth)acrylic acid copolymer, for example, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, etc. The crosslinking agent has two reactive groups. The crosslinking agent is used to increase the crosslinking degree of the adhesive and improve the mechanical properties of the cured adhesive product.

[0024] In some embodiments of the present invention, the mass of the silane coupling agent is 0.1-0.5% of the mass of the (meth)acrylic acid copolymer, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc. The silane coupling agent can improve the compatibility of the components in the adhesive and improve the adhesion of the adhesive.

[0025] To achieve the second object of the present invention, the present invention provides an adhesive film, which includes an adhesive layer composed of an acrylic adhesive with good recovery performance of any of the above schemes. It can be seen that the adhesive film provided by the present invention has good room temperature and high temperature bending performance and recovery performance, and can meet the various use environment requirements of flexible devices. Even in a high temperature environment, the adhesive film can take into account the excellent performance of bending action while still maintaining excellent recovery. The adhesive layer can be obtained by light curing the acrylic adhesive.

[0026] In some embodiments of the present invention, the thickness of the adhesive layer is 25-100 μm. When the thickness of the adhesive layer is within the above range, it can meet the use requirements.

[0027] In some embodiments of the present invention, the adhesive film further comprises a first release film and a second release film, and the adhesive layer is located between the first release film and the second release film. The release film can provide protection for the adhesive layer, facilitating the manufacture, storage, transportation and use of the adhesive film.

[0028] To achieve the third object of the present invention, the present invention provides a flexible device, which has an adhesive film according to any of the above schemes. The flexible device includes a foldable device, a rollable device, etc. The flexible device may be, for example, an image display device. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be further described in detail below through specific embodiments.

[0030] The names of the raw materials represented by the abbreviations in the formulations of Examples 1-3 and Comparative Example 1 are shown in Table 1 below.

[0031] Table 1 Abbreviations of raw material names

[0032]

[0033]

[0034] Preparation of (meth)acrylic acid copolymer:

[0035] Example 1-3: As shown in Table 2, accurately weigh corresponding proportions of 2-ethylhexyl acrylate, isostearyl acrylate, hydroxybutyl acrylate, cyclized polymer monomer, and dimethyl benzoate, and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Stir and introduce nitrogen. After stirring for at least 30 minutes, prepare the prepolymer by photoinitiated polymerization.

[0036] Comparative Example 1: As shown in Table 2, corresponding proportions of 2-ethylhexyl acrylate, isostearyl acrylate, hydroxybutyl acrylate, and dimethyl benzoate were accurately weighed and placed in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Nitrogen was introduced while stirring. After stirring for at least 30 minutes, a prepolymer was prepared by photoinitiated polymerization.

[0037] Preparation of adhesive:

[0038] Examples 1-3 and Comparative Example 1: Accurately weigh 100 parts of the corresponding prepolymer, add corresponding proportions of Oligomer A (weight average molecular weight of about 5000 g / mol, molecular weight distribution of about 2.0), 1,6-hexanediol diacrylate, and Silquest A-187 to the prepolymer as shown in Table 2, stir it evenly and let it stand for degassing to obtain glue.

[0039] Table 2 Formulation

[0040]

[0041]

[0042] Preparation of adhesive film:

[0043] Use the light release film R701T-C and the heavy release film R703T-C, place them up and down with their release surfaces facing each other, pour the above glue between the two films, control the thickness by roller extrusion and use UVA band irradiation curing under UV lamp to prepare a 50μm thick optical adhesive sheet.

[0044] Performance Testing:

[0045] The optical adhesives prepared in the above Examples 1-3 and Comparative Example 1 were respectively made into OCA tapes and the relevant properties were measured. The test method is as follows and the results are shown in Table 3.

[0046] 180 degree peel force test: GB / T 2792-2014;

[0047] Storage modulus: TA hybrid rheometer DHR-2, ASTM D4440-15;

[0048] Creep recovery test: TA rheometer applies a shear stress of 10 kPa, and the recovery time is 600 s;

[0049] Dynamic bending test: radius 3mm, 40 times / min, 50,000 times.

[0050] Table 3 Test results

[0051]

[0052]

[0053] The above test results show that the optical adhesive film prepared by the scheme of the embodiment of the present invention can make the prepared optical adhesive film have good creep recovery performance at 25°C and 65°C, and the ratio of the loss tangent value tanδ(65°C) at 65°C to the loss tangent value tanδ(25°C) at 25°C is tanδ(65°C) / tanδ(25°C) < 1. Moreover, the optical adhesive film prepared by the method provided by this patent has good adhesive performance while having low modulus.

[0054] Finally, it should be emphasized that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An acrylic adhesive having good recovery properties, characterized in that The acrylic adhesive has a creep value of more than 90% at 25°C, a recovery value of more than 85% at 25°C, a creep value of more than 80% at 65°C, and a recovery value of more than 85% at 65°C; The acrylic adhesive has a ratio of a loss tangent value tanδ(65°C) at 65°C to a loss tangent value tanδ(25°C) at 25°C, tanδ(65°C) / tanδ(25°C)<1.

2. The acrylic adhesive with good recovery performance according to claim 1, characterized in that The storage modulus of the acrylic adhesive at -20°C is less than 100 kPa, and the storage modulus at 65°C is greater than 15 kPa.

3. An acrylic adhesive with good recovery performance according to claim 1 or 2, characterized in that The acrylic adhesive has a creep value of more than 95% at 25°C, a recovery value of more than 90% at 25°C, a creep value of more than 85% at 65°C, and a recovery value of more than 90% at 65°C; The ratio of the loss tangent value tanδ(65℃) of the acrylic adhesive at 65℃ to the loss tangent value tanδ(25℃) at 25℃ is tanδ(65℃) / tanδ(25℃)<0.9; The storage modulus of the acrylic adhesive at -20°C is 80 kPa or less, and the storage modulus at 65°C is 18 kPa or more.

4. An acrylic adhesive with good recovery performance according to claim 1 or 2, characterized in that The acrylic adhesive comprises a (meth)acrylic acid copolymer having a structural unit derived from the following cyclopolymerizable monomer: Wherein R is a hydrocarbon group or a substituted hydrocarbon group.

5. The acrylic adhesive with good recovery performance according to claim 4, characterized in that The mass proportion of the structural unit of the cyclopolymerizable monomer in the (meth)acrylic acid copolymer is 0.5 to 10%.

6. The acrylic adhesive with good recovery performance according to claim 5, characterized in that The (meth)acrylic acid copolymer further comprises structural units derived from alkyl acrylate and hydroxyalkyl acrylate; The alkyl acrylate is selected from at least one of 2-ethylhexyl acrylate, n-butyl acrylate, lauryl (meth)acrylate, isooctyl acrylate, and isostearyl acrylate, and the hydroxyalkyl acrylate is selected from at least one of hydroxyethyl acrylate, hydroxybutyl acrylate, and hydroxypropyl acrylate; The mass proportion of the structural unit of the alkyl acrylate in the (meth)acrylic acid copolymer is 80 to 98%.

7. The acrylic adhesive with good recovery performance according to claim 4, characterized in that The acrylic adhesive further comprises an acrylate oligomer, a cross-linking agent and a silane coupling agent; The mass of the acrylate oligomer is 2-5% of the mass of the (meth)acrylic acid copolymer; the weight average molecular weight of the acrylate oligomer is 2000-9000 g / mol, preferably 3000-8000 g / mol; the molecular weight distribution of the acrylate oligomer is below 2.7; The mass of the cross-linking agent is 0.1-0.5% of the mass of the (meth)acrylic acid copolymer; the cross-linking agent has two reactive groups; The mass of the silane coupling agent is 0.1-0.5% of the mass of the (meth)acrylic acid copolymer.

8. An adhesive film, characterized in that The adhesive layer comprises an acrylic adhesive having good recovery performance as claimed in any one of claims 1 to 7.

9. An adhesive film according to claim 8, characterized in that The thickness of the adhesive layer is 25 to 100 μm; The adhesive film further includes a first release film and a second release film, and the adhesive layer is located between the first release film and the second release film.

10. A flexible device comprising an adhesive film according to claim 8 or 9.